2018
DOI: 10.3389/fpls.2018.00944
|View full text |Cite
|
Sign up to set email alerts
|

Genome Reduction in Tetraploid Potato Reveals Genetic Load, Haplotype Variation, and Loci Associated With Agronomic Traits

Abstract: The cultivated potato (Solanum tuberosum) has a complex genetic structure due to its autotetraploidy and vegetative propagation which leads to accumulation of mutations and a highly heterozygous genome. A high degree of heterozygosity has been considered to be the main driver of fitness and agronomic trait performance in potato improvement efforts, which is negatively impacted by genetic load. To understand the genetic landscape of cultivated potato, we constructed a gynogenic dihaploid (2n = 2x = 24) populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 62 publications
3
36
0
Order By: Relevance
“…In this study, for the first time, a high-throughput simplified 2b-RAD sequencing technique approach was used to identify and mark genetic segments for complex quantitative traits in potatoes. Segments with a large difference in specific tags were identified in chromosome 4 and 5, and further tag validation showed that the genetic segment in chromosome 5 is associated with the early maturity trait, which is consistent with previous studies [2,3,4,8,9,10,18]. …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, for the first time, a high-throughput simplified 2b-RAD sequencing technique approach was used to identify and mark genetic segments for complex quantitative traits in potatoes. Segments with a large difference in specific tags were identified in chromosome 4 and 5, and further tag validation showed that the genetic segment in chromosome 5 is associated with the early maturity trait, which is consistent with previous studies [2,3,4,8,9,10,18]. …”
Section: Discussionsupporting
confidence: 90%
“…Later, it was found that the major QTLs that control maturity in chromosome 5 were closely related to the QTLs controlling late blight resistance, but they were independent from each other and closely linked to the GP21 marker [7]. Tetraploid potatoes (2 n = 4× = 48) are highly heterozygous and have a high frequency of genetic recombination and a complicated genetic ratios [8]. It is much more difficult to conduct genetic analysis with tetraploid material than with diploid potatoes.…”
Section: Introductionmentioning
confidence: 99%
“…Combined with the availability of statistical tools that enable the utilization of allele dosage information (i.e., the number of copies of each allele at a given polymorphic locus), it is now possible to significantly increase the power of SNP information to detect recombination events and to incorporate this information into QTL mapping [ 5 7 ]. To date, this approach has been successfully used to detect novel QTLs and candidate SNPs associated with late blight resistance [ 4 , 8 ], internal heat necrosis [ 9 ], Potato virus Y [ 10 ], and agronomic traits [ 11 ], but largely unexplored for studying processing quality and other high-value traits with complex inheritance.…”
Section: Introductionmentioning
confidence: 99%
“…This is because one individual can carry more than two alleles at a locus and these alleles can be present in different dosages. The information about allele dosage is important for genetic studies, because a wide range of allelic combinations can occur at a locus that can result in different phenotypes [1][2][3][4] Similar to diploids, SNP genotyping has become state-of-art in polyploids. High-throughput genotyping often is performed by the use of conventional SNP arrays [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%